Options CSA et CIS pour la gestion intégrée des ravageurs et des maladies dans l’élevage au Sénégal - Sow, Fafa (International Livestock Research Institute, 2024)
This PPT presents options for climate-smart agriculture (CSA) and climate information services (CIS) to manage pests and diseases in livestock farming in Senegal. It addresses the management of animal health risks, such as Rift Valley Fever (RVF), through climate forecasting and surveillance systems. Adaptation practices such as unlimited watering, vaccination and avoidance of heat stress have led to a 15% improvement in milk production and increased adoption of preventive measures by beneficiaries.